The Value of Curiosity The Story of Chistopher Columbus - Johnson, Spencer (Value Communications, Inc. La Jolla, CA, 1977)
Demonstrates the value of curiosity in the life of Christopher Columbus.
8 - 10 years
Keywords: Columbus, Chirstopher; Discovery and exploration -- America -- Juvenile literature; Explorers -- Spain -- Biography; Curiosity -- Juvenile literature